ANALISIS BIBLIOMETRIK BUDAYA ORGANISASI DALAM PENDIDIKAN - Priatna, Asep (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study conducts a comprehensive bibliometric analysis to map the global research trends on organizational culture within educational organizations. The analysis identifies a significant growth in scholarly publications on this subject, indicating an escalating academic interest over time. The research output is geographically concentrated, with the United States, the United Kingdom, and Indonesia emerging as the predominant contributors to the literature. Through the examination of these publications, the study delineates the central themes and evolving trends that characterize the current discourse on organizational culture in the educational sector. The findings suggest a dynamic field of study with diverse areas ripe for further investigation. This work not only provides a valuable overview of the existing research landscape but also serves as a guide for future scholarly endeavors in understanding the complexities of organizational culture in educational settings.